2017
DOI: 10.1097/iae.0000000000001493
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Pharmacokinetics and Pharmacodynamics of Intravitreal Aflibercept, Bevacizumab, and Ranibizumab

Abstract: After monthly intravitreal injections, the systemic exposures of aflibercept, bevacizumab, and ranibizumab were distinct and correlated with different reductions in plasma free–vascular endothelial growth factor, which could provide biologic plausibility for potential differences in systemic adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
255
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(283 citation statements)
references
References 57 publications
11
255
2
2
Order By: Relevance
“…Zehetner et al [46] showed that IVB reduces serum VEGF levels for at least a month, while ranibizumab does not reduce serum VEGF levels significantly in adult patients treated for diabetic macular edema (DME) and age-related macular degeneration (ARMD). Similarly, Avery et al [47] revealed that bevacizumab decreases serum free VEGF levels more than ranibizumab in adult patients treated for DME, ARMD, and retinal vein occlusion. In a recent study, Wu et al [48] investigated the effects of IVB and IVR on serum VEGF levels in patients with type 1 ROP.…”
Section: Discussionmentioning
confidence: 94%
“…Zehetner et al [46] showed that IVB reduces serum VEGF levels for at least a month, while ranibizumab does not reduce serum VEGF levels significantly in adult patients treated for diabetic macular edema (DME) and age-related macular degeneration (ARMD). Similarly, Avery et al [47] revealed that bevacizumab decreases serum free VEGF levels more than ranibizumab in adult patients treated for DME, ARMD, and retinal vein occlusion. In a recent study, Wu et al [48] investigated the effects of IVB and IVR on serum VEGF levels in patients with type 1 ROP.…”
Section: Discussionmentioning
confidence: 94%
“…The systemic effect of anti-VEGF agents has been a concern since these drugs became first-line therapy for several intraocular conditions, even though only small amounts of the anti-VEGF drugs are released from the eye into the systemic circulation [28, 30]. While intraocular VEGF is a critical mediator of angiogenesis involved in the pathogenesis of diseases such as nAMD, DME, and RVO (retinal vein occlusion), systemic VEGF acts as a vascular protective factor essential for maintaining the integrity and antithrombogenic properties of the endothelium [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eyes that had more treatment before the switch were more likely to have greater visual improvement. Possible reasons for the significant anatomical and functional response seen with aflibercept may be due to its differing pharmacokinetic and pharmacodynamics properties and the greater disease activity in these patients . Aflibercept features a higher binding affinity to VEGF‐A and to additional growth factors released during angiogenesis such as VEGF‐B and PIGF, in contrast to inactivation of only VEGF‐A with bevacizumab and ranibizumab .…”
Section: Discussionmentioning
confidence: 99%